2011
DOI: 10.2298/jsc100801104k
|View full text |Cite
|
Sign up to set email alerts
|

A facile synthesis of phenazine and quinoxaline (new 1,4-benzo diazine) derivatives using magnesium sulfate heptahydrate as a catalyst

Abstract: Convenient and simple procedures for the synthesis of phenazine and quinoxaline derivatives were developed via a reaction of o-phenylenediamines and 1,2-dicarbonyl compounds. In addition, the synthesis of two new 1,4-benzodiazine derivatives and the catalytic activity of magnesium sulfate heptahydrate (MgSO 4 ·7H 2 O) in the room temperature condensation of o-phenylenediamines and 1,2-dicarbonyl compounds in ethanol as solvent are reported. This method has many appealing attributes, such as excellent yields, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…From a synthetic perspective, chemical reactions for synthesizing linear conjugated polymers, such as the Suzuki cross-coupling reaction, 28,29 Yamamoto reaction, 30,31 Sonogashira-Hagihara reaction, 32,33 oxidative coupling, 34,35 Schiff-base reaction, 10,36 cyclotrimerization, 37,38 phenazine ring fusion reaction 39,40 and Friedel-Crafts arylation, 41,42 are effective for the preparation of CMPs. The diversity of building blocks, coupled with the wide availability of different reaction types, make CMPs an invaluable platform for developing new organic porous materials.…”
Section: Introductionmentioning
confidence: 99%
“…From a synthetic perspective, chemical reactions for synthesizing linear conjugated polymers, such as the Suzuki cross-coupling reaction, 28,29 Yamamoto reaction, 30,31 Sonogashira-Hagihara reaction, 32,33 oxidative coupling, 34,35 Schiff-base reaction, 10,36 cyclotrimerization, 37,38 phenazine ring fusion reaction 39,40 and Friedel-Crafts arylation, 41,42 are effective for the preparation of CMPs. The diversity of building blocks, coupled with the wide availability of different reaction types, make CMPs an invaluable platform for developing new organic porous materials.…”
Section: Introductionmentioning
confidence: 99%
“…In connection with our previous programs on synthesis of organic compounds, [20][21][22][23] in this work, we wish to report a simple and convenient synthesis of octahydroquinazolinones/thiones 4 by reaction of aromatic aldehyde 1, urea/thiourea 2, and cyclic 1,3-dione 3, in the presence of catalytic amount of In(OTf) 3 under solvent-free conditions (Scheme 1). The yield of products was good to excellent without the formation of octahydoxanthenes 5, which is the major product of the procedure reported by the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Karami and co‐worker studied the synthesis of various phenazines and quinoxalines using magnesium sulfate heptahydrate (MgSO 4 ⋅7H 2 O) as an effective, cheap and non‐toxic catalyst based on the condensation of 1,2‐dicarbonyl compounds with o ‐phenylenediamines . To prove the general applicability of the method few azatriphenylene derivatives have been synthesized by the reaction of 9,10‐phenanthrenequinone ( 7 ) with corresponding 1,2‐diamines ( 42 ).…”
Section: Synthetic Approaches Towards Azatriphenylene Derivatives:mentioning
confidence: 99%
“…In addition, this methodology is also applicable for the synthesis of sterically hindered azatriphenylene derivative such as tetrapyrido- Karami and co-worker studied the synthesis of various phenazines and quinoxalines using magnesium sulfate heptahydrate (MgSO 4 ⋅7H 2 O) as an effective, cheap and non-toxic catalyst based on the condensation of 1,2-dicarbonyl compounds with o-phenylenediamines. [36] To prove the general applicability of the method few azatriphenylene derivatives have been synthesized by the reaction of 9,10-phenanthrenequinone (7) with corresponding 1,2-diamines (42). In addition, it was found that 1,2-pyridinediamine underwent the condensation with compound 42 to produce dibenzo [f,h] (46) in 77 % yield.…”
Section: Synthesis Of Di-azatriphenylenesmentioning
confidence: 99%